Pigmented/melanocytic malignant perivascular epithelioid cell tumor with TFE3-SFPQ(PSF) rearrangement – a challenging diagnosis of PEComa family of tumors - Szumera-Cieækiewicz, Anna; Kuczkiewicz-Siemion, Olga; Seliga, Katarzyna; Grabowska-Kierył, Magdalena; Tysarowski, Andrzej; Wągrodzki, Michał; Świtaj, Tomasz; Prochorec-Sobieszek, Monika; Rutkowski, Piotr (Polish Journal of Pathology, 2019)
We here report a case of a distinct subtype of pigmented/melanocytic malignant PEComa with TFE3-SFPQ(PSF) rearrangement. The tumor involved the iliac region and clinically mimicked metastatic melanoma. The immunohistochemical assessment was supplemented with molecular studies including fluorescence in situ hybridization (FISH) and next-generation sequencing sarcoma panel (NGS). We also discuss the differential diagnosis of intraabdominal PEComas and emphasise the recent molecular reports on the TFE3 rearranged tumors.